Youth ministry that transforms a comprehensive analysis of the hopes, frustrations and effectiveness of today's youth workers - Strommen, Merton, P.; Jones, Karen E. 1956-; Rahn, David, 1954- (Grand Rapids, MI Zondervan, 2001)
Includes bibliographical references and index.
Keywords: Church work with youth